Learning Management in Improving the Quality of Graduates Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in Sukabumi District - Usman Armaludin; Iim Wasliman; Deti Rostini (UIN Sunan Gunung Djati Bandung, 2021)
This research is motivated by the existence of an interesting phenomenon in the implementation of Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in Sukabumi Regency. The regional government 's very strong attention to religious education in Sukabumi District , the lack of conditions for MDTA infrastructure, inadequate learning management at MDTA, limited sources of activity funds, and the structure of the MDTA curriculum that has not been fully understood have become the focus of problems in this research. This study presents the results of research on Learning Management in Improving the Quality of Madrasah Diniyah Takmiliyah Awaliyah Graduates in Sukabumi District. This study is a qualitative research with descriptive methods were performed on MDTA in three (3) the District, the District, Cicantaya n , Caringin and Cisaat. The data collection technique combines field observations, in-depth interviews and documentation studies. Inductive data analysis resulted in the following conclusions: in general, the management of Learning in Improving the Quality of Madrasah Diniyah Takmiliyah Awaliyah Graduates (MDTA) in Cicantayan, Caringin and Cisaat Districts, Sukabumi Regency has not run optimally. In particular, first, the policy product of the Sukabumi Regency Government in the provision of education at MDTA has been successfully implemented even though the realization of the operational assistance budget and the pattern of guidance and supervision are still not optimal. Second, the achievements of the results of the implementation of learning at MDTA so far have been sufficient to meet the graduation standards of students, but in the implementation of learning activities still do not meet the standards of the learning process. Third, there are some inhibiting factors faced in the form of limited budget, weak understanding of the methodology and the mindset of teachers in learning, inadequate learning facilities, and the absence of a national madrasah diniyah curriculum standard. Fourth, the future demands are in the form of community support for the development of MDTA with a modern and innovative perspective, the formation of the diniyah teachers' deliberation forums and the professional training of teachers. Fifth, several improvements have been made in the form of holding MDTA accreditation and strengthening the Diniyah Takmiliyah Communication Forum (FKDT). And the sixth is the impact obtained from the implementation of education at MDTA in the form of a religious community environment, holding back the moral decadence of the younger generation and creating religious figures in the Cicantayan, Caringin and Cisaat Districts. This study also offers a hypothetical model for the application of learning management to MDTA.